Transient stability enhancement for a power system - Ho, Sy Ha. (2013)
The ability of a power system to return to stable operating condition after the occurrence of disturbance is its stability. With the growing in size of the modern power systems, it becomes more difficult to maintain stability. Under large disturbance, the response is fluctuating and some part of the system can be damaged. Thus, improving the transient stability of a power system is one of the most important tasks for electrical engineers. This project will concentrate on design of an advanced PID controller for power system transient stability enhancement. A single machine infinite bus (SMIB) system is considered to study small-signal stability and to design controller. Normally, a power system stabilizer (PSS) plays the control role in a power system. It provides damping for electrical torque through adding an extra signal to the excitation system. But the performance of PSS is not guaranteed when load condition is changed. The PID controller, on the other hand, offers more options to control the response. It is able to reduce overshoots, lower settling time or eliminate steady-state error, etc. Then, it can be implemented to improve transient stability of the power system. The design methods in this project may be further applied to multi-machine power system